Indonesia-China Economic Resilience Amid Political Volatility: Sustainable Cooperation After the 2025 Social Unrest - Huswatun Miswar Syarifah (Journal of Governance and Global Studies, 2025)
Uncertainty concerning the political implications arising from the unprecedented social unrest occurring in August 2025 raises challenges in the economic partnership between Indonesia and China. At the minimum, social unrest and nationwide protests in Indonesia have consequences beyond the domestic circumstance and condition of prosperity: they impact the resilience and dynamic of a more than seven decades economic partnership. This work to explore and explain how this bilateral partnership withstands challenges, and adapts, from a geostrategic and disintegrating Indonesia social resilience, and bilateral resilience economic diplomacy policy fundamentally symmetrical in nature and fungible at point of equilibrium containment. Indonesia and China bilateral economy and resilience have reached multidisciplinary and integrative layer. Although this gives the academic and research community theoretical and practical constructive bundle that explains and packages adaptive uncertainty, it also, and to a greater extent, extends to public policy, business, and economic relationships, the opportunity to explore sustainable partnership provision in politically asymmetric context and condition. Future research aimed at strengthening and substantiating the economic resilience of Indonesia and China will, and should, make the intent and substance of this paper very relevant.